Retention of Organic Matter Contained in Industrial Phosphoric Acid Solution by Raw Tunisian Clays: Kinetic Equilibrium Study. (11th November 2013) - Hamza, Wiem; Chtara, Chaker; Benzina, Mourad
Abstract : Purification of industrial phosphoric acid (H3 PO4 ) is considered a major problem and several methods have been evaluated. In this study, two different types of clay, raw bentonite clay (RBC) and raw grey clay (RGC), were used for removal of SOM contained in H3 PO4 at low pH. The used samples were characterized by X-ray diffraction, chemical analysis, and specific surface area and MET was also realized. The ability of clay samples to remove S.O.M from aqueous solutions of industrial phosphoric acid has been studied at different operating conditions: temperature, agitation speed, contacting time, and so on. The results indicated that adsorption is an exothermic process for lead S.O.M removal. The equilibrium adsorption data were analysed using the Langmuir and Freundlich isotherms. The results showed that the equilibrium adsorption capacities for the two adsorbents followed best the Langmuir model. Thermodynamic parameters showed that the adsorption process was spontaneous and exothermic.